Flow of the Amery Ice Shelf and its tributary glaciers - Pittard, ML; Jason Roberts; Roland Warner; Benjamin Galton-Fenzi; Christopher Watson; Richard Coleman (2013)
The Amery Ice Shelf (AIS) is a major ice shelf that drains approximately 16% of the East Antarctic Ice Sheet. Here we use a sequence of visible spectrum Landsat7 satellite images to track persistent surface features over the southern portion of the AIS and its three major tributary glaciers. A spatially incomplete velocity field is calculated by comparing the distances features have moved between image pairs. Key features of the flow field including the vorticity and strain rate distributions are discussed. Our velocities agree with results from recent compilation of satellite derived velocities and available Global Position System (GPS) measurements. To assess change, we compare the yearly average velocities from image pairs in 2006 and 2010 over the study region. We find the velocities show minimal changes with the exception of the Mellor Glacier which has increased.